Teaching Across Borders: Lived Experiences of Internationally Trained Mathematics Educators in Their Early U.S. Careers - Calbi, Jamera S.; Diano, Felix Jr (RIRAI Publisher, 2025)
The U.S. faces a shortage of qualified mathematics teachers, prompting the recruitment of internationally trained educators (ITEs), particularly from the Philippines, recognized for strong content knowledge and pedagogy. Despite their expertise, Filipino ITEs encounter challenges in classroom management, curriculum alignment, and parent engagement during their early U.S. teaching careers. This study employed a descriptive phenomenological design to examine the lived experiences of 17 Filipino ITEs with up to three years of U.S. teaching experience. Data were collected via semi-structured virtual interviews, transcribed verbatim, and analyzed using Colaizzi’s seven-step method. Five themes emerged: navigating classroom management, aligning curriculum with U.S. standards, building relationships with parents and the community, developing cultural and pedagogical competence, and seeking professional support while maintaining resilience. Participants adapted to new behavioral norms, instructional pacing, and culturally nuanced communication through mentorship, reflective practice, professional learning communities, and culturally responsive teaching. Findings highlight that early career success depends on pedagogical, cultural, and institutional adaptability. Implications emphasize culturally responsive induction, structured mentorship, targeted professional development, and administrative guidance to support teacher effectiveness, retention, and student outcomes.